Phacoemulsification Combined With Supra-Capsular and Scleral-Fixated Intraocular Lens Implantation in Microspherophakia: A Retrospective Comparative Study - Chen, Ze-Xu; Zhao, Zhen-Nan; Sun, Yang; Jia, Wan-Nan; Zheng, Jia-Lei; Chen, Jia-Hui; Chen, Tian-Hui; Lan, Li-Na; Jiang, Yong-Xiang (Frontiers in Medicine, 2022)
Background: Microspherophakia (MSP) is a rare ocular condition, the lens surgery of which is complicated by both insufficient zonules and undersized capsule. Methods: This study included MSP eyes managed with phacoemulsification combined with supra-capsular and scleral-fixated intraocular lens implantation (SCSF-IOL) and made the comparison with those treated by transscleral-fixated modified capsular tension ring and in-the-bag intraocular lens implantation (MCTR-IOL). Results: A total of 20 MSP patients underwent SCSF-IOL, and 17 patients received MCTR-IOL. The postoperative best corrected visual acuity was significantly improved in both groups (P < 0.001), but no difference was found between the groups (P = 0.326). The IOL tilt was also comparable (P = 0.216). Prophylactic Nd:YAG laser posterior capsulotomy was performed 1 week to 1 month after the SCSF-IOL procedure. In the SCSF-IOL group, two eyes (10.00%) needed repeated laser treatment and one eye (5.00%) had a decentered capsule opening. Posterior capsule opacification was the most common complication (6, 35.29%) in the MCTR group. No IOL dislocation, secondary glaucoma, or retinal detachment was observed during follow-up. Conclusions: SCSF-IOL is a viable option for managing MSP and is comparable with the MCTR-IOL. Nd:YAG laser posterior capsulotomy was necessary to prevent residual capsule complications after the SCSF-IOL procedure.